MEWUJUDKAN DEMOKRASI INDONESIA SESUAI KEPRIBADIAN BANGSA DARI PRESPEKTIF STRATEGI PERANG SEMESTA - Agape Zacharia RD; Lukman yudho Prakoso; Helda Risman (Sekolah Tinggi Pariwisata Mataram, 2022)
Democracy that implemented in the life order of the state and nation of Indonesia has reflected the face of Pancasila democracy, which is characterized by deliberation. From several choices of democratic methods, it can be found that the best and right strategy can be used as a model of democracy that applies the principles of Pancasila. By using the concept of strategy theory, and total war theory, as well as other theories to evaluate each other from existing theories. Research methodology through literature study to examine and analyze secondary data that addresses the issues discussed. It is important that democracy in Indonesia does not emulate any country according to the identity and personality of the Indonesian people.